Working days series in Colombia: an application to industrial growth adjustment - García, Álvaro Montenegro (Universidad Pedagógica y Tecnológica de Colombia, 2014)
While many economists are aware of the effect of workdays on production measures, it is common to find data being analyzed without adjustment. Generally, the number of workdays in a month changes from one year to the next. This is true for all months, not only for March and April which exhibit the largest variations due to the Holy Week. This paper constructs a series of workdays, accounting for changes in holidays through time, and uses it to adjust industrial production data from DANE. Some months the difference between industrial growth reported by DANE and growth adjusted by workdays may reach 12 percentage points, positive or negative.